2021
DOI: 10.1021/acscatal.1c02056
|View full text |Cite
|
Sign up to set email alerts
|

Classical Polymers as Highly Tunable and Designable Heterogeneous Photocatalysts

Abstract: Photocatalysis has emerged as a powerful synthetic tool to facilitate redox reactions with the target of creating stable and tunable photocatalytic materials. A class of recyclable photocatalytic materials has emerged through the combination of classical polymers with photocatalytic small molecules. Classical polymers are inexpensive and easy to produce. They can be used to create cheap, easily recyclable, and reusable materials. Moreover, these materials can be imparted with a broad range of functionality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 93 publications
0
38
0
Order By: Relevance
“…This combination produces a new hybrid material class of photocatalytically active polymers. 53 Here, we have designed photocatalytic hydrogels, where only the photocatalytic moieties absorb visible light, as illustrated in Scheme 1. The copolymerization of photocatalytic small molecules with classical monomers produces highly efficient photocatalytic gels.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination produces a new hybrid material class of photocatalytically active polymers. 53 Here, we have designed photocatalytic hydrogels, where only the photocatalytic moieties absorb visible light, as illustrated in Scheme 1. The copolymerization of photocatalytic small molecules with classical monomers produces highly efficient photocatalytic gels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, our group has described the synthesis of a new class of photocatalytic classical polymers. The copolymerization of photocatalytic small molecules, modified with vinyl functionality, and classical monomers, combines the versatility of classical polymers with photocatalytic activity. This combination produces a new hybrid material class of photocatalytically active polymers …”
Section: Introductionmentioning
confidence: 99%
“…Classical polymer photocatalysts have recently emerged as an alternative to conjugated photocatalytic systems. 5 Here, a small molecular photocatalyst is modified so that it can be incorporated into a classical polymer. This incorporation can be during the polymerisation of the polymer, or as a post-polymerisation modification.…”
Section: Self-assembled Polymer Photocatalystsmentioning
confidence: 99%
“…3,4 Furthermore, the incorporation of small molecule photocatalysts into classical polymers has recently been reported as new heterogeneous photocatalytic systems. 5…”
Section: Introductionmentioning
confidence: 99%
“…7 Their advantages include precise control of conjugation lengths, cost-effectiveness, chemical robustness, and variability of properties through facile synthesis and direct access to the toolbox of classical polymer chemistry. 8,9 A few studies undertaken to date showed their promising potentials in synthesis and photocatalytic applications but barely included systematic investigations of structure−property relationships. 10−12 In particular, the effect of monomer composition remains unclear.…”
Section: ■ Introductionmentioning
confidence: 99%